2005
DOI: 10.1016/j.ejcnurse.2005.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Women's Social Support and Social Network after Their First Myocardial Infarction; A 4-Year Follow-Up with Focus on Cardiac Rehabilitation

Abstract: There is a need to develop CRPs that are specifically designed for women based on their age and family relationships. Nurses' training programmes should place greater emphasis on cardiac rehabilitation from the perspective of women with focus on professional support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 50 publications
(56 reference statements)
1
14
0
Order By: Relevance
“…A common and essential dimension in women's recovery is their relationships with other people (social dimension). The women in this study value the support from family and friends, as well as sharing thoughts with other women in the same situation during their recovery process, which is confirmed in other studies (Doiron-Maillet & Meagher-Stewart, 2003 ; Mendes et al, 2010 ; Pryor, Page, Patsamanis, & Jolly, 2014; Svedlund & Danielson, 2004 ; White, Hunter, & Holttum, 2007 ; Wieslander, Baigi, Turesson, & Fridlund, 2005 ) and is evident as a contributing factor for health (Sjöström-Strand & Fridlund, 2006 ; White et al, 2007 ). Social support is also a contributory factor for men's recovery (Kristofferzon, Löfmark, & Carlsson, 2003 ; Pryor et al, 2014).…”
Section: Discussionsupporting
confidence: 84%
“…A common and essential dimension in women's recovery is their relationships with other people (social dimension). The women in this study value the support from family and friends, as well as sharing thoughts with other women in the same situation during their recovery process, which is confirmed in other studies (Doiron-Maillet & Meagher-Stewart, 2003 ; Mendes et al, 2010 ; Pryor, Page, Patsamanis, & Jolly, 2014; Svedlund & Danielson, 2004 ; White, Hunter, & Holttum, 2007 ; Wieslander, Baigi, Turesson, & Fridlund, 2005 ) and is evident as a contributing factor for health (Sjöström-Strand & Fridlund, 2006 ; White et al, 2007 ). Social support is also a contributory factor for men's recovery (Kristofferzon, Löfmark, & Carlsson, 2003 ; Pryor et al, 2014).…”
Section: Discussionsupporting
confidence: 84%
“…In addition, a lack of social support from family and friends has been reported to be a barrier to CR enrollment. 54 …”
Section: Resultsmentioning
confidence: 99%
“…This is supported by Meleis et al [35] who describes that confirmation, counseling and feedback are presumptions in order to get a successful transition to health. Earlier research has shown that the length of time of recovery for women, who received support from health care professionals throughout CRP, was shorter than for women who did not receive this support [37]. Therefore, it is essential that the CRNs support the women both in their clinical and personal recovery [14,16,17,19] and give the women the opportunity to an individually designed secondary prevention.…”
Section: Discussionmentioning
confidence: 99%